MARKET CHANNELS OF LABU SIAM (Sechium edule (Jacq.) Sw) IN SUKANALU VILLAGE KARO DISTRICT NORTH SUMATERA - Tambunan, Herlina Yolanda; Manik, Rianta Chen Yohana (Institute of Computer Science (IOCS), 2024)
The purpose of this study is to describe chayote's marketing channel in the study region. To investigate the marketing functions performed by producers to chayote intermediate dealers in the research region. To examine marketing expenses, marketing margins, and farmers' share in chayote marketing in the research region. To assess the effectiveness of chayote marketing channels in the research region. The data obtained included both primary and secondary data. The data analysis approach is descriptive, with results summarized by kind. The results indicated that: 1) The chayote marketing channel in Sukanalu Village is divided into three (three) channels. Channel I consists of farmers, village collecting traders, district wholesalers, MMTC wholesalers, Aksara retailers, and consumers. Channel II: Farmers - District Traders - Main Market Retailers - Consumers, District Traders - Simpang Kuala Retailers - Consumers. Channel III: Farmers, District Collecting Traders, MMTC Wholesalers, Fishing Rod Retailers, and Consumers. 2) The chayote marketing channel in the research region is efficient, with efficiency values of 38% in channel I, 25.71% in channel II, and 19.59% in channel III.